2021
DOI: 10.1007/s10096-021-04199-1
|View full text |Cite
|
Sign up to set email alerts
|

Vulvovaginal candidiasis and current perspectives: new risk factors and laboratory diagnosis by using MALDI TOF for identifying species in primary infection and recurrence

Abstract: Vulvovaginal candidiasis (VVC), considered the second cause of genital infection among women, has pathogenic mechanisms still to be elucidated and unknown risk factors. Prevalence studies with laboratory diagnosis (at first diagnosis and recurrence) are uncommon, especially using MALDI TOF, used in this clinical, epidemiological, and laboratory study for evaluating candidiasis, and identifying unknown risk factors. To obtain clinical and epidemiological data, patients were questioned, and there was material co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 72 publications
1
12
0
2
Order By: Relevance
“…Pereira et al found that 62.2% of women with candidiasis were symptomatic while 37.8% were asymptomatic. 10 Vaginal smear examination revealed that the most candida infections (13 patients or 52%) were experienced by pregnant women in the 3rd trimester of pregnancy. Among those in 2nd trimester of pregnancy, seven patients (28%) were positive for candidiasis, and the lowest candida infection was experienced by pregnant women during the first trimester of pregnancy (five patients or 20%).…”
Section: Resultsmentioning
confidence: 97%
“…Pereira et al found that 62.2% of women with candidiasis were symptomatic while 37.8% were asymptomatic. 10 Vaginal smear examination revealed that the most candida infections (13 patients or 52%) were experienced by pregnant women in the 3rd trimester of pregnancy. Among those in 2nd trimester of pregnancy, seven patients (28%) were positive for candidiasis, and the lowest candida infection was experienced by pregnant women during the first trimester of pregnancy (five patients or 20%).…”
Section: Resultsmentioning
confidence: 97%
“…(33) benzer bir çalışmada, kromojenik agar ve MALDI-TOF MS yöntemi ile doğruladıkları vajina kökenli 79 C. albicans izolatından 75'inde germ-tüp oluşumu bildirmişlerdir. Çalışmamızda, referans yöntem olarak kullanılan MALDI-TOF MS, maya türlerinin identifikasyonu için yaygınlaşmaya başlayan bir yöntemdir ve %90'ın üzerinde özgüllüğe sahiptir (33) . Ayrıca, Erdem ve ark.…”
Section: Discussionunclassified
“…Generalmente las infecciones genitales trasmitidas por hongos no se consideran enfermedades de trasmisión sexual, sin embargo, pueden ocurrir con menor frecuencia, además, son condiciones que pueden aumentar morbilidad en personas con inapropiadas prácticas sexuales (50), dentro de las enfermedades producidas por hongos se incluyen la vulvovaginitis y la balanitis, que son causadas por el hongo cándida albicans, que forma parte de la microbiota vaginal normal en la mujer por lo que generalmente no se le considera como de trasmisión sexual en la mujer, mientras que, en los hombres sí se considera como una infección de transmisión sexual frecuente (50,51).…”
Section: Infecciones Micóticas Protozoarias Y Ectoparasitarias De Tra...unclassified